2019
DOI: 10.1111/jam.14381
|View full text |Cite
|
Sign up to set email alerts
|

A new acridone with antifungal properties againstCandidaspp. and dermatophytes, and antibiofilm activity againstC. albicans

Abstract: Aim:The increase in the number of fungal infections worldwide, coupled with the limitations of current antifungal chemotherapy, demand the development of safe and effective new antifungals. Here, we presented the synthesis of a novel acridone (M14) and its antifungal properties against Candida and dermatophytes species. Methods and Results: A series of 17 acridones was designed, synthesized and tested for its antifungal activity. The minimum inhibitory concentration (MIC) was determined by the broth microdilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Candida albicans is found in mucosal surfaces and in the gastrointestinal and genitourinary tracts and is the most common cause of systemic and invasive infections. The fungus easily colonizes host tissues and indwelling medical devices (Ramage et al ., 2005), such as urinary catheters, dental materials, artificial heart valves, joint prostheses, penile implants and intrauterine devices (Sardi et al ., 2013; de Oliveira et al ., 2019; Handorf et al ., 2019). Furthermore, biofilms are often tolerant to conventional antifungal therapeutics and the host immune system (Nobile et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans is found in mucosal surfaces and in the gastrointestinal and genitourinary tracts and is the most common cause of systemic and invasive infections. The fungus easily colonizes host tissues and indwelling medical devices (Ramage et al ., 2005), such as urinary catheters, dental materials, artificial heart valves, joint prostheses, penile implants and intrauterine devices (Sardi et al ., 2013; de Oliveira et al ., 2019; Handorf et al ., 2019). Furthermore, biofilms are often tolerant to conventional antifungal therapeutics and the host immune system (Nobile et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Microscopic evaluation of C. albicans hyphal growth in the presence of M14 revealed that the yeast-to-mycelia transformation was completely inhibited. Similarly, severe inhibition of hyphal growth of Trichophyton rubrum was shown [16].…”
Section: Antifungal and Antibiofilm Activitymentioning
confidence: 93%
“…Recent studies have allowed researchers to obtain a selective derivative M14 ( Figure 2D) with anticandidal and anti-dermatophyte activity and low toxicity to human fibroblasts [16]. M14 exhibited growth-inhibitory activity against all reference and clinical strains of Candida and dermatophytes (MIC range 7.81-31.25 μg mL -1 ).…”
Section: Antifungal and Antibiofilm Activitymentioning
confidence: 99%
“…A report published in 2019 by the Centers for Disease Control and Prevention ( CDC, 2019 ) stated that Candida albicans presents a serious threat via the spread of life-threatening candidiasis ( Ostrosky-Zeichner et al, 2010 ; CDC, 2019 ). C. albicans and its biofilms are found on mucosal surfaces and in the gastrointestinal and genitourinary tracts, and C. albicans readily colonizes host tissues and indwelling medical devices such as urinary catheters, dental implants, artificial heart valves, joint prosthetics, penile implants, and intrauterine devices ( Ramage et al, 2005 ; Sardi et al, 2013 ; De Oliveira et al, 2019 ; Handorf et al, 2019 ). Highly structured C. albicans biofilms form on implant surfaces and subsequently the pathogen disseminate into blood to cause invasive candidiasis, which is responsible for an estimated 100,000 deaths per annum in the United States and for the replacement of over five million central nervous catheters ( Sardi et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%